2020
DOI: 10.1002/bab.1849
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of human IgG Fc fragments that expose regulatory rheumatoid factor neoepitopes and may show promise as antirheumatic agents

Abstract: Previously, we showed that immunoglobulin G (IgG) Fc fragments can expose neoepitopes specific to antibodies that were named regulatory rheumatoid factor (regRF). RegRF confers resistance to experimental autoimmune diseases. Immunization of rats with rat Fc fragments exposing neoepitopes recognized by regRF reduces the symptoms of collagen‐induced arthritis. Therefore, IgG Fc fragments that expose neoepitopes recognized by regRF are promising antirheumatic agents and regRF‐producing lymphocytes are potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We have previously shown that the binding of healthy human sera to tanned IgG‐loaded erythrocytes does not change in the presence of IgG 7,8 . On this basis, we concluded that IgG does not carry neoepitopes recognized by regulatory rheumatoid factor 7,8 .…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…We have previously shown that the binding of healthy human sera to tanned IgG‐loaded erythrocytes does not change in the presence of IgG 7,8 . On this basis, we concluded that IgG does not carry neoepitopes recognized by regulatory rheumatoid factor 7,8 .…”
Section: Resultsmentioning
confidence: 70%
“…We have previously shown that the binding of healthy human sera to tanned IgG-loaded erythrocytes does not change in the presence of IgG. 7,8 On this basis, we concluded that IgG does not carry neoepitopes recognized by regulatory rheumatoid factor. 7,8 In the course of this study, we found that lyophilized ( Figure 2B) and non-lyophilized IgG preparations also did not affect the binding of rheumatoid arthritis sera to tanned IgG-loaded erythrocytes.…”
Section: Conformers Of Human Igg Fc Fragmentsmentioning
confidence: 76%
See 3 more Smart Citations